Skala Ekonomi, Produktivitas dan Bank Syari’ah Indonesia - Endang Kurniati (Fakultas Ekonomi dan Bisnis Islam, 2016)
This study aims to determine the internal performance of Islamic commercial bank in allocating resources efficiently by using analytical approach productivity and economies of scale. The model used is a model of translog production function with the dependent variable (dependent) financing and independent variables (independent) of capital, labor, and third party funds. Translog models estimated consist of four criteria of the model, that model of translog complete, translog models without a quadratic function, translog models without the interaction between factors, and translog model of constant elasticity of substitution (CES). Selection of the best model on a production function translog done through statistical test, so that the best model is used to reflect the value of the output elasticity and returns to scale. The results of this study are: (1) The model chosen is the model of constant elasticity of substitution. (2) Variable input third party funds had the largest productivity value compared with variable capital and labor. (3) In the study period, the condition of diseconomies of scale occur on Islamic Banks, which means Islamic Banks have not been able to produce output increased financing with cheaper production costs.